Institutional support of foreign economic activity of Kazakhstan - Nabiyev, E.N.; Bazarova, S.K.; Daribekov, S.S. (BUKETOV BUSINESS REVIEW, 2019)
In the article the problems of institutional support of foreign economic relations of the country are considered. The classification of Russian scientists on the integration of institutions of foreign economic activity into four groups is given: regulation, assistance, stimulation, control and calculation. For the purpose of institutional support of foreign economic activity of Kazakhstan, the need for a system approach was stressed. The characteristic is given to organizations that manage the foreign economic activity of the republic. Since the Republic of Kazakhstan is a member of the World Trade Organization, the Eurasian Economic Union, it was stressed that the institutional support of its foreign economic activity should be brought in the line with the requirements of these organizations. Based on the analysis of the dynamics of the foreign trade turnover of the Republic of Kazakhstan, it was concluded that its decline in recent years has been affected by the global financial and economic crisis and, as a result, the deterioration of market conditions. In the future, recommendations were made on improving the institutional support system for non-commodity exports in order of qualitative change of the export structure, development of finished products based on competitive high technologies in the world markets and increase of the share of products of processing industry. In order to improve the commodity structure of imports entering the Republic of Kazakhstan, the need for institutional support for import-substituting domestic producers was stressed. As a result of the research, recommendations were made to continue work to bring the investment climate of Kazakhstan in the line with international standards and to improve the work on providing benefits to investors implementing the projects in the non-primary sectors of the country.